'A question of earnings', 1987 (1987)
1987 1960-2000 "'A question of earnings', 1987" [EP0039], 1987 'A question of earnings : a study of the earnings of blue collar employees in London local authorities' was produced by LEVEL - the London Equal Value Steering Group - in 1987. This analysis of manual workers found that men earned more than female colleagues on the same grade. This disparity between men's and women's total earnings was largely due to bonus, overtime and other plus payments.